PRESTASI BELAJAR MAHASISWA PENERIMA BEASISWA BIDIK MISI FMIPA UNM TAHUN AKADEMIK 2010/2011 - Hamka L., .; Hartono, . (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2012)
DOWNLOAD PDFThe research was a descriptive study to see how the student learning achievement of bidik misi awardees at the beginning of academic year 2010/2011. Population and sample in this study were all students which received bidik misi scholarship at Faculty of Mathematic and Natural Science, Makassar State University (FMIPA UNM). Method collecting data by taking the documentary secondary of GPA at beginning semester. The data obtained in this study were analyzed using descriptive statistical and categorized according academic guidance of Departement of Biology FMIPA UNM year 2010. Study showed that the average learning achievement of students were very satisfactory with average GPA 3.01. There were 12.28% of students who in honors category (cumlaude, GPA 3.51 to 4,00). While, 57.89% of students in category of very satisfactory (GPA 2.76 to 3.50), and 26.32% in the category satisfying (GPA 2.50 to 2.75). Nevertheless, there have about 1.75% of students in the category enough (GPA 2.00 to 2.49), and also 1.75% of students in less category (GPA 0.00 to 1.99). Key words: Learning achievement, bidik misi scholarship